Green Preparation of Nano-Curcumin Extract and its Applications on Klebseilla Pneumoneiae and Staphylococcus Aureus - Abdullah Hamad Najim; Hussain Salih Akbar; Najdat Bahjat Mahdi (Central Asian Journal of Medical and Natural Science, 2025)
This study aims to identify the inhibitory effect of curcumin extract and iron oxide nanoparticles synthesized by co-precipitation method from curcumin extract as a reducing agent, and to test their antimicrobial activity against Klsensiella pneumoniae and Staphylococcus aureus using disk diffusion method. The nanoparticles were characterized using (XRD, SEM, Zeta sizer, zeta potentioal, VSM) techniques, where the crystalline size of the nanoparticles was . 26.8nm and the surface morphology of the particle tends to form spherical clusters with an average hydrodynamic size of 27.58 nm and has a negative charge of about -29.7mV and the zeta size examination showed about 256.4 nm and the particles showed a saturation magnetization of about. The results indicated that the aqueous curcumin extract did not show any inhibitory effect on the bacterial isolates, while the alcoholic extract gave the highest inhibition diameter at a concentration of 500 mg/ml 8 mm for K. pneumoniae. As for the curcumin extract with nano iron oxide, the inhibition diameters for K. pneumoniae at concentrations (600, 500, 400, 300, 200, 100 μg/ml) were (15, 13, 11. , 9, 7, 5) mm, respectively. As for S. aureus, the average inhibition diameters at the same concentrations were (18, 17, 14, 13) mm.